Temperature dependence in Bragg edge neutron transmission measurements. Issue 4 (30th July 2022) - Al-Falahat, Ala'a M.; Kardjilov, Nikolay; Woracek, Robin; Boin, Mirko; Markötter, Henning; Kuhn, Luise Theil; Makowska, Malgorzata; Strobl, Markus; Pfretzschner, Beate; Banhart, John; Manke, Ingo
Abstract : A systematic study was carried out to investigate the neutron transmission signal as a function of sample temperature. In particular, the experimentally determined wavelength‐dependent neutron attenuation spectra for a martensitic steel at temperatures ranging from 21 to 700°C are compared with simulated data. Abstract : A systematic study has been carried out to investigate the neutron transmission signal as a function of sample temperature. In particular, the experimentally determined wavelength‐dependent neutron attenuation spectra for a martensitic steel at temperatures ranging from 21 to 700°C are compared with simulated data. A theoretical description that includes the Debye–Waller factor in order to describe the temperature influence on the neutron cross sections was implemented in the nxsPlotter software and used for the simulations. The analysis of the attenuation coefficients at varying temperatures shows that the missing contributions due to elastic and inelastic scattering can be clearly distinguished: while the elastically scattered intensities decrease with higher temperatures, the inelastically scattered intensities increase, and the two can be separated from each other by analysing unique sharp features in the form of Bragg edges. This study presents the first systematic approach to quantify this effect and can serve as a basis, for example, to correct measurements taken during in situ heat treatments, in many cases being a prerequisite for obtaining quantifiable results.